Variational Methods and Parallel Solvers in Chemo‐Mechanics. Issue 1 (25th January 2021) - Kiefer, Björn; Rheinbach, Oliver; Roth, Stephan; Röver, Friederike
Abstract: This study represents a first step towards tailored solvers for chemo‐mechanical multi‐field problems in a variational setting.